EVOLUTION OF ENTREPRENEURIAL CONTRACTS DEVELOPMENT: BRIEF HISTORICAL DIGRESSION - Marukyan, Gayane (International Journal of Innovative Technologies in Social Science, 2023)
The scientific assumptions on this or that legal phenomenon are based on its’ historical development and legal understanding. The entrepreneurial contracts have their great role in the development of business relations regulation. The article refers to the phenomenon and gives light to the legal framework and understanding of the contract and its role in different time periods on the development of business relations.